INONDATIONS TORRENTIELLES EN ZONES MONTAGNEUSES AFFÉRENTES AU GOLFE DU MEXIQUE - JEAN-NOËL SALOMON (Revue Roumaine de Géographie)
Global warming is no longer contested by the scientific community since there are numerous proofs attesting to it (ice-melt, rising sea levels, ecological modifications, instrumental measurements, information processing, simulations, etc). One of its mainconsequences is increased evaporation of the oceans which stimulates cyclogenesis. In fact, cyclones have been more frequent and devastating mainly over the past few decades (Katrina in August 2005; Nargis in May 2008), unleashing catastrophic floods. Faced with this situation, various countries took on a differentstance. Some of them reacted moderately (Cuba), others with indifference, or relied on their technology (US). The study of several major disasters (Mitch, Katrina, Wilma, etc.) teaches us some lessons. However, certain catastrophic floods were not covered by the media, e.g. the ETCE (Extreme Tropical Climatic Events). Twoexamples are illustrative in this respect: the Panama and Tabasco (Mexico) events (November 2006 and November 2007, respectively). The consequences of these devastating floods were many casualties andmaterial damage over large areas. After a time, erosion processes become more numerous with disastrous soil loss, particularly in mountainous areas (slopes), moreover so, if used for farming or grazing. Eventually, after a longer lapse of time, the environment grew unfriendly (Haiti’s example is unfortunately convincing), so that people began migrating, even going abroad (diasporas). The example of mountainous areas in the Mexican Gulf, Caribbean Sea, shows that climate change was by no means minor, the renewed outbreak of natural disasters triggered by global warming having a major detrimental impact on the environment and the economy with severest consequences for the poorest populations, who can hardly cope with such hazards, a situation that may result in grave social problems.